Il «concilio» di Gerusalemme, le tensioni ecclesiali e l’opera dello Spirito - Manzi, Franco (La scuola cattolica, 2025)
The Jerusalem Assembly (A.D. 49/50) was the Church’s first Spirit-prompted attempt to resolve disputes that had arisen regarding the evangelization of the Gentiles. Despite the letter sent by the Jerusalem assembly to the Christian communities, the conflicts escalated. Therefore, Paul did his best, in the face of strong opposition in the Church, to spread that decision taken in common. It was precisely Paul’s letters, in which the Church would later identify the inspiration of the Spirit, that gave rise to a new wave of tensions, caused by heretical misrepresentations of the concept of justification by faith alone. Such misunderstandings were clarified by the Letter of James, which, recognized as inspired, pointed to the saving efficacy of faith expressed in works of charity. Thus, for the NT, the Spirit propels the Church toward ll truth, not simply in spite of tensions, but often through them.